The results of the development of a personalized method of mandibular foramen searching in the aspect of mproving the efficiency and safety of inferior alveolar nerve block (Эндодонтия Today)
The position of mandibular foramen and its correspondence with the mandibular nerve are the key positions of the personified research. The ideas of different anatomic schools about the positions of mandibular foramen are based on their own research of native, clinical, radiological materials and on the averaged common tendencies. Aim. It was the development, anatomical and clinical evaluation of the effectiveness of the individual method of finding the projection of the mandibular foramen on the ramus of mandible.Materials and methods. The study was conducted on 200 adult (from 20 to 45 years) cadaveric mandibles with the preserved (saved) height of the alveolar process in the distal part from December 2018 to April 2019. Linear measurements based on points С1-С2; М(с1-с2); С1-А; R-A; R- M were carried out with the help of caliper in cm. To assess the effectiveness of the proposed method, a numerical rating scale for pain estimation in combination with the Wong-Baker facial scale in adaptation for single use was used.Results. Thus we received an anatomical and mathematical model of projection point of mandibular foramen (F) on the upper surface of the ramus of mandible according to the results of measurement. On the basis of anthropometric studies a predictive calculation of the depot area for local anesthetic while using the proposed method of anesthesia was done. An approximate position of the needle tip when immersed in 2/3 of the length is projected on mandibular foramen slightly behind and upwards of the lingula of the mandible. The effectiveness of mandibular anesthesia is estimated within the limits from 77,6% to 89,4 %. Recently, there has been an increased interest in personalization in dentistry, both globally and in individual methods and means. Special significance of the personification evident in the value of an anatomo-topographical and constitutional peculiarities of patients. The study of pain sensation in the process of the treatment of mandible dental diseases with the use of classical and modified methods showed a high level of efficiency, as well as the absence of a statistically significant difference between the results. The absence of significant difference proves the clinical efficiency of the proposed model of finding the injection area mark points.